2008
DOI: 10.1177/1352458508097922
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of tumefactive demyelinating lesions using MR imaging and in-vivo proton MR spectroscopy

Abstract: Clinical features along with several MRI characteristics such as open ring enhancement, peripheral restriction on DWI, venular enhancement, and presence of Glx on spectroscopy may be rewarding in differentiating TDLs from neoplastic lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
86
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(90 citation statements)
references
References 26 publications
(39 reference statements)
3
86
1
Order By: Relevance
“…A high lipid peak in PCNSLs and a variable lip-lac peak in patients with TDL have been previously noted by many other researchers. 1,3,10,15,16 In our study, we classified the lip-lac grade by visual judgment, which could easily be applied in daily clinical practice. We found that a high-grade lip-lac (grade Ͼ3) was mostly shown in PCNSLs regardless of whether there was necrosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A high lipid peak in PCNSLs and a variable lip-lac peak in patients with TDL have been previously noted by many other researchers. 1,3,10,15,16 In our study, we classified the lip-lac grade by visual judgment, which could easily be applied in daily clinical practice. We found that a high-grade lip-lac (grade Ͼ3) was mostly shown in PCNSLs regardless of whether there was necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, elevated Cho and decreased NAA peak were observed in both PCNSLs and TDLs and are consistent with the findings of previous reports. 10,15,16 The increase in Cho is thought to result from rapid membrane turnover, high mitotic activity, and dense cellularity in PCNSL and from inflammatory cellular infiltration, reactive astrogliosis, and demyelination in TDL. 13,16,24 The decreased NAA reflects the neuronal destruction, axonal damage, early axonal degeneration, and decreased axonal density.…”
Section: Discussionmentioning
confidence: 99%
“…10 Recently, 2 imaging findings of TDLs have been reported. Malhotra et al 11 found peripheral restricted diffusion on DWI in 11 of 18 patients with TDLs, while Masu et al 12 observed that intralesional fibers appeared to be a pyramidal tract on diffusion tractography in a patient with TDL. Conversely, the perilesional hyperintense FA rim that is frequently found in the perifocal edema of high-grade gliomas 13 has not been described in TDLs.…”
mentioning
confidence: 99%
“…Leptomeningeal enhancement is not a feature of MS, and its presence was highlighted by an international consensus panel as a "red flag" to consider other nondemyelinating etiologies. 23 In contrast, the MR imaging parameter of "acute diffusion restriction," while highly characteristic of vascular occlusion such as stroke, [29][30][31] has also been a feature recently reported in acute demyelinating lesions, particularly tumefactive lesions, 32,33 and therefore was retained in the final tool. In developing the MR imaging scoring tool, we considered the challenges of MR imaging acquisition in the pediatric context.…”
Section: Discussionmentioning
confidence: 99%